An exploratory study of collaboration among early childhood development non-profit organisations in the Western Cape Province - Kusikwenyu, Schwarzenegerr (Department of Social Development, 2016)
Collaboration among Early Childhood Development Non-Profit Organisations (ECD NPOs) in South Africa is an unexplored area of research. Little is known about the ECD NPO sector, let alone the strategies they employ to remain viable, effective and efficient in the face of a declining resource base. Collaboration is one of these strategies and it is hoped that this qualitative research will make a contribution to the understanding of the state of collaboration among ECD NPOs in the Western Cape Province. The study explores how ECD NPOs and government participants understand collaboration in this sector, and investigates the factors that are considered before entering past and present collaboration initiatives. The study further explores the value of collaboration, and the factors enabling and those inhibiting collaboration among ECD NPOs in the Western Cape Province. Nineteen (19) face-to-face in-depth interviews were conducted with participants from sixteen (16) ECD NPOs and three (3) government departments. The study revealed that ECD NPO and government participants had a common understanding of collaboration. ECD NPOs considered various factors such as capacity, time/time frame, cost and benefit analysis, partner's track record and the need for service before engaging in collaborative initiatives, while government participants only considered capacity (human resources and expertise) and collaborating partner's track record before engaging. The study indicated that there were more benefits than challenges to collaboration among ECD NPOs. In addition, the study established that the factors enhancing collaboration among ECD NPOs in the Western Cape include shared or similar vision, good working relationships, networking, common knowledge and understanding of the ECD sector and an open mind approach. On the other hand, the factors inhibiting collaboration among ECD NPOs include shortage of resources, competitiveness, time constraints, organisational culture differences, fear of the unknown and geographical location. Participants spoke positively about their collaboration experiences and noted how this would be a strategy to pool resources and enhance their survival, effectiveness and efficiency in service delivery in the ECD NPO sector.